The pro-community of children and young people in the family - Prokosz, Małgorzata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
Acting on behalf of other people in times marked by individualization and domocentrism seems to be an abstract task. Families raise their children firstly as good students, but then motivate them to a career, better earnings and prestige. This text tries to answer the questions: Do Polish families form pro-community in their descendants? What does it manifest itself in their homes? How can it be developed?
Keywords: pro-community; family; children; youth; strengthening pro-community behaviours